Error Analysis of SMA Pangudi Luhur Bandar Lampung Students’ Translation in Using Meaning-Based Translation. - Kefas Ajie Bhekti (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The purpose of this research is to analyze the errors of SMA Pangudi Luhur Bandar Lampung Students’ Translation in Using Meaning-Based Translation. This research focuses on discovering the errors that may arise, and the most dominant type of error in students’ translation. After analyzing the students’ translation, the result shows that there are many errors in students’ translation. Those errors include Global Errors, Local Errors, Omission Errors, Addition Errors and Misformation Errors. Global Errors and Local Errors are parts of Communicative Effect Taxonomy while the others are parts of Surface Strategy taxonomy. The errors that writer found were divided based on two taxonomies. The percentage of Global Errors in this research is 4.83% while the percentage of Local Errors is 95.1%. The percentage of Omission Errors is 45.6%, the percentage of Addition Errors is 19.2%, and the percentage of Misformation Errors is 35.2%. After quantifying the students’ translation, it can be concluded that almost all errors from two taxonomies arise in the students’ translation and the most dominant errors in this research are Local errors and Omission errors.